2011
DOI: 10.1177/104063871102300224
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simple Polymerase Chain Reaction—Based Diagnostic Assays for GM2 Gangliosidosis Variant 0 (Sandhoff-Like Disease) in Japanese Domestic Cats

Abstract: Abstract. Polymerase chain reaction (PCR)-based assays combined with microchip electrophoresis were developed and evaluated for diagnosis and genotyping of GM2 gangliosidosis variant 0 (Sandhoff-like disease) in Japanese domestic cats. A preliminary genotyping survey was carried out in the population of Japanese domestic cats (1,015 cats in total) in southern Japan. Three kinds of assays including PCR primer-induced restriction analysis (PIRA) and mutagenically separated (MS)-PCR were carried out using blood-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…32 In mixed breed cats in Japan, it is reported that the allele frequency for a single mutation of GM2 gangliosidosis variant 0 is less than 0.1%. 21 In the present study, the carrier frequency of the canine CLN5 single mutation (c.619C >T) was 8.1% in the population of Border Collies in Japan. Although there is no objective criterion to evaluate the degree of frequency, the carrier frequency of NCL in Border Collies in Japan may be very high compared with those in other human and animal lysosomal diseases.…”
Section: Discussionsupporting
confidence: 42%
“…32 In mixed breed cats in Japan, it is reported that the allele frequency for a single mutation of GM2 gangliosidosis variant 0 is less than 0.1%. 21 In the present study, the carrier frequency of the canine CLN5 single mutation (c.619C >T) was 8.1% in the population of Border Collies in Japan. Although there is no objective criterion to evaluate the degree of frequency, the carrier frequency of NCL in Border Collies in Japan may be very high compared with those in other human and animal lysosomal diseases.…”
Section: Discussionsupporting
confidence: 42%
“…Microchip electrophoresis has recently attracted considerable attention in DNA and RNA analysis due to its high efficiency, high throughput, timesaving ability, easy operation, and low consumption of samples and reagents. 4,27,35 The use of microchip electrophoresis can markedly shorten the time for analysis of DNA fragment patterns, which is currently approximately 3 min per sample. Furthermore, gel electrophoresis requires hazardous substances (acrylamide) or mutagenic (ethidium bromide) and toxic (silver nitrate) stains as well as longer analytical time, whereas the use of toxic substances and expenses incurred for hazardous waste disposal can be avoided using microchip electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…MS-PCR was originally developed to be used for analysis of point mutations, 29 and was utilized for a single nucleotide substitution in several diseases or polymorphisms. 27,32 In the present study, however, MS-PCR was applied for detection of a 4-bp deletion mutation with a modification in the design of primers shown in Table 1. The molecular difference of amplified bands was enlarged by the length of the allele-specific primers, resulting in a lower concentration of agarose gel and the use of only 1 lane of electrophoresis for a genotype determination, compared to the LP analysis and 2-step PCR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the Japanese laboratory, molecular diagnostic tests for feline GM1 and GM2 gangliosidoses previously identified and molecularly defined in Japan were carried out using polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) methods [12,15]. The PCR-RFLP assay for feline GM1 gangliosidosis was slightly modified in the present study.…”
mentioning
confidence: 99%